The Impact of Nano-Concrete in Contemporary Architecture - Wijdan Deyaa Abdul Jalil; Husaein Ali Hasan Kahachi (Wasit Journal of Engineering Sciences)
The rapid development in technology of building materials and systems could be easily observed these days in the huge building advances such as achieving building sizes, shapes, forms and speed of building which could never be achieved by using ordinary building materials. One of the interested break overs in building materials technologies is Nano-Concrete. Nano-Concrete is the substance of adding nanomaterial to concrete. Nano-concrete has special specifications and properties when compared with the ordinary concrete mixes such as adding Nano SiO2, Nano TiO2 and Carbon Nano tubes to improve performance and structural resistance. This extended the limits of building technologies thus enabling architects to achiev more complex forms with higher performance, or giving the concrete special properties such as light pass-through concrete or self-compacting concrete.